AUTOMATED WASTE COLLECTION CONTAINER LID OPENER PROTOTYPE WITH DISINFECTANT SPRAYER AS PART OF NOSOCOMIAL INFECTION PREVENTION - Fatahah Dwi Ridhani (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2021)
Nosocomial infection is a health issues related to the in-hospital activities. One of the indirect cause was the contamination related to the waste disposal activity. All hospital waste was deemed hazardous that it needs extra care during collection. Cross contamination may arises when the waste containers was not treated. To alleviate the problem and to promote healthy habits, this article describe a smart disinfectant sprayed waste collection container and its status reports. By automating the lid opening and closing that was triggered by human proximities using passive infrared detector and ultrasound sensor, it provide convenience in waste disposal. This also prevent cross contamination related with physical contact with the waste container which may induce the nosocomial infection. The container also tracking its remained waste capacity and will report when it was almost full to prevent overflowed and to alarmed for immediate waste pickup. In case of delayed container collection, the lids will remain closed and the light indicator turn to red. The indicator will turn green in normal conditions and turn yellow if the container was almost full. ESP32 was used to interface with ultrasound sensors to approximate the container remaining capacity. Passive infrared sensor and a servo motor was linked to actuates the lid opening and closing. Some disinfectant was sprayed for every detected increase in waste level. The disinfectant aerosol canister was pushed by a DC motor. For reporting, the systems was equipped with LoRa for status report. This systems was tested inside Poltekkes Kemenkes Jakarta II building and could reach at least 80m distance from the report center for reporting.